2017
DOI: 10.1002/2017jd027034
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of northern Tibetan Plateau on East Asian summer rainfall via modulating midlatitude transient eddies

Abstract: Roles of the Tibetan Plateau (TP) in forming and changing the seasonal Asian climate system have been widely explored. However, little is known about modulation effects of the TP on extratropical transient eddies (TEs) and subsequent synoptic responses of the East Asian rainfall. In this study, the Community Atmosphere Model version 5.1 coupled with a slab ocean model is employed to highlight the important role of the TP in regulating the upper‐tropospheric transient wave train. Comparison between sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…In the following, we will concentrate on analysing the stationary water vapour transport. Considering that Northeast Asia is under the control of the mid‐latitude westerly, extratropical cyclones and transient vortex are active and have close connections with the moisture budget anomalies during individual precipitation events (Sun et al ., 2010; Xie et al ., 2012; Deng et al ., 2017). Hence, further studies are needed to demonstrate the role of the transient water vapour transport for these events, which is beyond the scope of this study.…”
Section: Resultsmentioning
confidence: 99%
“…In the following, we will concentrate on analysing the stationary water vapour transport. Considering that Northeast Asia is under the control of the mid‐latitude westerly, extratropical cyclones and transient vortex are active and have close connections with the moisture budget anomalies during individual precipitation events (Sun et al ., 2010; Xie et al ., 2012; Deng et al ., 2017). Hence, further studies are needed to demonstrate the role of the transient water vapour transport for these events, which is beyond the scope of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the meridional position of the North America continent plays a fundamental role in determining the size of NAM, while the Rocky Mountains act to amplify this effect. These results are generally consistent with previous studies (e.g., Xu et al ., 2009; Deng et al ., 2017; He, 2017). Moreover, the roles of other large terrains in shaping the NAM deserve further investigation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the NAM region is bounded by the geography and topography, such as Mexican Plateau, Sierra Madre Occidental and the Rocky Mountains, which would help to shape the monsoonal circulation features via the mechanical and thermal effects (Tang and Reiter, 1984; Adams and Comrie, 1997; Gutzler et al ., 2009; Varuolo‐Clarke et al ., 2019). However, the dynamic and thermal effects of large terrains on circulation and precipitation in the adjacent areas are still being debated (e.g., Liang et al ., 2006; Deng et al ., 2017). In this study, the Rocky Mountains are moved southwards along with the continent; thus, whether or not the presence of the Rocky Mountains is the dominant factor for the NAM is not studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations